Pengaruh Life Style, Kualitas Produk dan Store Image terhadap Keputusan Pembelian - Astri Ayu Purwati; Yusrizal Yusrizal; Indah Cipta Ramadhani (IPM2KPE, 2019)
The purpose of this research is to find out and analyze the influence of life style, product quality, and store image on consumer purchasing decisions atMulia InternationalStore Fashion Sukaramai PlazaPekanbaru.The method used is multiple linear regression analysis.The sample used was 100 respondents.The results of this study indicate that life style and product quality have a significant effect on purchasing decisions, while store image has no significant effect on consumer purchasing decisions inMulia InternationalStore Fashion Sukaramai PlazaPekanbaru. Keywords: Life Style, Product Quality, Store Image, Purchasing Decision.